Anthropometric and performance characterization of U16 and U18 female handball Portuguese national teams - Carvalho, A. M.; Gouveia, P.; Mesquita, J.; Pineu, I.; Sá, C.; Sá, P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Handball is an invasion team sport, characterized with high levels of impacts, change of direction and intermittent efforts1. Due to all the dimensions that it comprises - technical, tactical, psychological/social and physical characteristics - handball is a very complex sport 2. Each player has its own unique cognitive or physical characteristics that somehow are more suitable for each playing position2. For this reason, it is important to highlight the features that coaches should search when pursuing those differentiated players that might be suitable for national team. This topic gains more importance when it comes to female handball, where research is only growing in the recent years 1,2. The purpose of this study was to characterize the physiological profile of the Portuguese young female handball players.